Effect of tillage systems on the level of contamination of nonarable land of Zhytomyr Polissya - Borisenko, V.I. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The results of studies of the effects of different systems of the basic soil cultivation on weediness of land that is withdrawn from agricultural use in Zhytomyr Polissya are presented in the article. The effect of different tillage systems on the main species composition of annual and perennial weeds and quantitative composition of organs of vegetative propagation of perennial weeds is described. It was established that on land that is withdrawn from economic use in Zhytomyr Polissya, the application of different systems of the basic soil cultivation reduces weediness of lands to 53.7%. The smallest development of annual and perennial weed species occurs mainly during combination tillage.